Az európai büntetőjog fejlődésének irányai a Lisszaboni Szerződés után - Farkas Ákos (Szegedi Tudományegyetem Állam- és Jogtudományi Kar Szeged, 2012)
In the European Union the aims of criminal law can no longer be achieved on a purely national basis. The range of criminal law must not be limited by national borders but it should become transnationally effective. A new branch of law the European criminal law emerged in the last twenty years in order to serve these aims. This contribution sketches the development and the main institutions of the European criminal law from the Maastricht Treaty to the Lisbon Treaty.
Keywords: Társadalomtudományok; Jogtudomány